(untitled) (REMUNOM, 2025)
The family assistance plan market generates huge amounts of money annually; however, plans such as life insurance and funeral plans generate fear in consumers, as they are preparation for death. The objective is to analyze the behavior and attitude of consumers who have a plan, or not, in relation to family assistance plans. As a methodology, 130 people were interviewed through non-probabilistic convenience sampling, on an agree/disagree scale, validated with Cronbach’s alpha at 0.884. The profile of the respondents resulted in 55% being male, and 45% female; as for age group, by distribution, 31% are up to 26 years old; 33% are between 27 and 37 years old; and 36% are over 38 years old; the average age is 34 years old. Furthermore, according to the survey, 32% of the respondents stated that they have an assistance plan; and another 68% do not. The main findings indicate that 95% believe that family assistance plans are necessary to provide security in difficult times; 93% believe that family assistance plans provide financial security; 91% believe it is important to be prepared for future unforeseen events; 93% believe it is appropriate for the assistance plan to have equipment for rent; 70% consider it relevant for a family assistance plan to have monthly raffles; 96% consider it important to know the benefits that family assistance plans can bring; 54% believe that discounts on medical appointments are a relevant benefit; and 93% consider it important for family assistance plans to offer cost-benefit. As a contribution, the study pointed out evidence about the consumer’s attitude towards the assistance plan product and what they consider most important in their demand.